2013
DOI: 10.1177/1050651913479926
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Public Relations in China

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Western countries are not the sole countries to use forms of promotion. In many other countries, such as in Russia or China as well as in the Global South, promotional communication is used actively in public affairs and political life (Chen and Culbertson, 2003; Hou et al, 2013; Tsetsura, 2011; Tsetsura and Chernov, 2009). Also, promotion is an important element between countries globally (Miskimmon et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Western countries are not the sole countries to use forms of promotion. In many other countries, such as in Russia or China as well as in the Global South, promotional communication is used actively in public affairs and political life (Chen and Culbertson, 2003; Hou et al, 2013; Tsetsura, 2011; Tsetsura and Chernov, 2009). Also, promotion is an important element between countries globally (Miskimmon et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Kiesenbauer and Zerfass (2015) focused on professionals’ conceptualization of strategic communication and found that chief communication officers viewed their mission as managing relationships with various stakeholders, while future communication leaders (Generation Y) held that reputation management remained of paramount importance for communication departments. Testing the potential paradigm shift against the Chinese context, Hou et al (2013) found that in-house practitioners saw PR as subordinate to organizational branding and marketing, while agency consultants conceived of PR as “the long-term and strategic communication through which public perceptions are delicately managed rather than as a means for developing organizational image” (p. 321). Hence, the field requires continued efforts to determine at what level either strategic orientation translates communication practice into the organization performance.…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…Networking embraces typical Eastern cultural characteristics represented by guanxi , which is defined by Bian (2006) as “a dyadic, particular and sentimental tie that has the potential of facilitating favor exchanges between the parties connected by the tie” (p. 312). The multiplexity of guanxi , which blends emotional values into instrumental functions, serves as the key to understanding multiple logics and identities of communication practices in China (Hou et al, 2013). In practice, networking activities fulfill a diversified set of functions and create productive benefits that facilitate the formation of interpersonal resources for Chinese practitioners (Huang, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Dialogue and dissent/protest PR concepts have gained increasing significance. Public relations affect new sources, and this fact can be seen in countries that have close economic and/or gaps on freedom of speech, such as China, North Korea, the Middle East countries (Avidar, 2011;Chen, Chen & Chen, 2012;Hou et al, 2013;Lahav, 2014). On the other hand, many studies have been conducted to understand internet use and its impact on public relations (PR) activities.…”
Section: Public Relations and Higher Education Institutionsmentioning
confidence: 99%